Microflora species and population analysis for feline sepsis treatment efficiency control - P. A. Rudenko (Ветеринария сегодня)
The paper presents data on microflora species and population analysis for feline sepsis treatment efficiency control using different schemes. Sepsis diagnostics demonstrated a significant (by 37.7%) prevalence of gram-negative microorganisms compared to gram-positive ones as well as the presence of Candida species which is indicative of severe purulent inflammation in experimental cats. The provided data also suggest that in the course of sepsis treatment intestinal microbe ecosystem stabilizes more effectively and tends towards healthy cat parameters in B3 group animals. On the seventh day of treatment the cats from the abovementioned group showed a significant decrease in the number of Staphylococcus, Streptococcus, Escherichia, Pseudomonas, Klebsiella, Citrobacter, Proteus and Candida species in their feces samples in comparison to samples tested before treatment. This happened in parallel to a significant increase in the number of probiotic microflora species, like Lactobacillus and Bifidobacterium in comparison to initial results. It was established that sepsis treatment was most effective in Group B3 cats where in average incarnations appeared 6.19 days earlier than in animals of B1 Group, primary lesions healed 9.91 days earlier and the total clinical improvement occurred 5.78 days earlier.